Transparent Cross-Flow Platform as Chemiluminescence Detection Cell in Cross Injection Analysis - Thachkorn Somboonsuk; Phoonthawee Saetear; Thitirat Mantim; Nuanlaor Ratanawimarnwong; Prapin Wilairat; Nathawut Choengchan; Duangjai Nacapricha (My University, 2023)
This work presents the use of a transparent 'Cross Injection Analysis' (CIA) platform as a flow system for chemiluminescence (CL) measurements. The CL-CIA flow device incorporates introduction channels for samples and reagents, and the reaction and detection channels are in one acrylic unit. A photomultiplier tube placed above the reaction channel detects the emitted luminescence. The system was applied to the analysis of (i) Co(II) via the Co(II)-catalyzed H2O2-luminol reaction and (ii) paracetamol via its inhibitory effect on the catalytic activity of Fe(CN)63- on the H2O2-luminol reaction. A linear calibration was obtained for Co(II) in the range of 0.002 to 0.025 mg L-1 Co(II) (r2 = 0.9977) for the determination of Co(II) in water samples. The linear calibration obtained for the paracetamol was 10 to 200 mg L-1 (r2 = 0.9906) for the determination of pharmaceutical products. The sample throughput was 60 samples h-1. The precision was ≤4.2% RSD. The consumption of the samples and reagents was ca. 170 µL per analysis cycle.
Keywords: Luminol; Flow injection analysis; Linear range; Analytical chemistry methods development